Level of awareness among female medical students towards risk factors of breast cancer at Faculty of Medicine, Udayana University, Bali, Indonesia - Daarshini Bhaskavan; Ni Nyoman Ayu Dewi; I Wayan Surudarma (Intisari Sains Medis, 2018)
Background: Breast cancer is the most commonly diagnosed cancer among women in the vast majority of countries worldwide that is triggered by several risk factors This study aims to determine the level of awareness among female medical students towards risk factors of breast cancer at Faculty of Medicine, Udayana University, Bali, Indonesia.Method: A cross-sectional descriptive study was conducted on 56 female medical students of Udayana University. A self-administered questionnaire consisting of 25 questions were used where 0 indicates for wrong answers or “don‟t know‟ and a one is given for the correct answer. A total score of >20 is considered having an excellent level of awareness, 16-20 for good level of awareness, 10-15 for moderate level of awareness, and < 10 means poor level of awareness.Result: Most of participants had moderate level of awareness (71.4%), followed by a poor level of awareness (17.9%), good level of awareness (10.7%), and there were no participants had high level of awareness (0%).Conclusion: Most female medical students had a moderate level of awareness towards risk factors of breast cancer.